2019
DOI: 10.1016/j.sjbs.2018.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of novel isolate Streptomyces sp., NLKPB45 from Nellore costal region for its biomedical applications

Abstract: Actinobacteria, which are the prolific producers of antibiotics and significant suppliers to the pharmaceutical industry, can produce a wide variety of bioactive metabolites. An actinomycete strain designated NLKPB45 was isolated from mangrove soils samples of Nellore coastal regions Andhra Pradesh and assessed for antibiotic production and activity against pathogenic bacteria. From a total of 9 mangrove soil samples, 143 acinomycetes were isolated. Among the isolated them 6 actinomycetes strains showed potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“… Al-Ansari et al (2019) reported the isolation of ten actinomycetes from the soil, of which five demonstrated activity against Enterobacter aerogenes and Proteus mirabilis . Kalyani et al (2019) isolated 143 actinomycetes, including a Streptomyces sp. NLKPB-45 showed activity against Gram-positive bacteria, S. aureus , and Gram-negative Escherichia coli and P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Al-Ansari et al (2019) reported the isolation of ten actinomycetes from the soil, of which five demonstrated activity against Enterobacter aerogenes and Proteus mirabilis . Kalyani et al (2019) isolated 143 actinomycetes, including a Streptomyces sp. NLKPB-45 showed activity against Gram-positive bacteria, S. aureus , and Gram-negative Escherichia coli and P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
“…against P. aeruginosa . Kalyani et al (2019) reported the activity of Streptomyces sp. NLKPB-45 against Gram-negative bacteria Escherichia coli and P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
“…The study showcases a strategy to circumvent the potential pitfalls of the evolutionary algorithm. It will allow us consistently construct an evolutionary correct model for a sequence dataset and will subsequently improve the prediction accuracy of several different types of biological studies, be it a sequence characterization (Guder and Krishna 2019;Kalyani et al 2019;Mallu et al 2019;Satyanarayana et al 2017;Somavarapu et al 2017;Vemuri et al 2019) or proteomic study (Jaswanthi et al 2019;Rao et al 2017;Samara Shekar Reddy et al 2019;Srideepthi et al 2017).…”
Section: Required Strategic Improvement Over the Existing Protocolsmentioning
confidence: 99%
“…It would also allow in extracting the evolutionarily closest templates for the protein sequences and would aid to improve the accuracy of the conventional template-based protein modeling protocols [82][83][84][85][86][87][88][89][90]. The strategy would be significantly useful for improving the algorithmic accuracy of several related research works including protein modeling [91] and folding [92] and functional enzymatic characterization [93][94][95][96][97][98][99][100].…”
Section: Crucial Residues For Functional Mutagenesis and Directed Evomentioning
confidence: 99%